Lektura Lubuskich podróży ze smakiem peregrynacją dla przyjemności i intelektualną wędrówką po wiedzę (spojrzenie filologa-lingwokulturologa - Węgorowska, Katarzyna (Colloquia Litteraria, 2023)
The extraordinary character of a contemporary ‘Baedeker’-type culinary-tourist guide,whichappeals to the senses of its reader, is perfect to showcase the region al specialties of the Lubuskie Region. Such a guide will also act as an inspiration to consider the richness and diversity of the Lubuskie Region. The subject, and thus the objective of this articleis to prezent Lubuskie’s culinary heritage and, throughit, the virtues of Lubuskie’s fauna and flora, the advantages of Lubuskie’s agrotourism farms and Lubuskie’s ethnotourism. The spiritual/symbolich eritagethatis preserved in this guideshows off the Lubuskie Region as an attractive are a where the past is an integral part of the present.